CLIMATE CHANGE AND TEACHER’S PERFORMANCE IN SECONDARY SCHOOL IN BENUE STATE NIGERIA - Ortsa, Mhenmbee Gabriel; Ndidiamaka, Akwam Jane (International Journal of Educational Management and Innovation, 2021)
The study investigated climate change and Teachers performance in secondary schools in Benue State, Nigeria.  Two research questions and two hypotheses guided the study.  Survey research design was adopted for the study.  The population compromised 5,225 teachers from 512 secondary schools. A total of 528 (10%) teachers from 51 (10%) secondary schools was sampled using proportionate stratified sampling technique: A 10-items self structured questionnaire titled “climate change and teachers performance questionnaire (CCTPQ) was used for data collection. The data were analyzed using mean and standard deviation to answer the research questions while chi-square (x2) test of goodness of fit was used to test the hypotheses at 0.05 level of significance.  The finding of the study revealed that rainfall has a significant impact on teachers’ performance in secondary school in Benue State, Nigeria. The study also found that excessive heat has a significant impact on teachers’ performance in secondary schools. it was concluded that climate change significantly impact on teachers performances in secondary school in Benue State, Nigeria.  Based on the findings, it was recommended among others that secondary, principals should provide rain-cut to teacher during raining season to enable them perform effectively and the government should provide Air-conditions or sling fans during excessive heat in the classrooms for efficient teahers performance.